One-year clinical evaluation of composite restorations in posterior teeth: Effect of adhesive systems - Sundfeld, Renato Herman [UNESP]; Scatolin, R. S.; Oliveira, F. G. [UNESP]; Machado, L. S. [UNESP]; Alexandre, R. S. [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP] (Operative Dentistry, 2012)
This clinical study assessed the performance of posterior composite resins applied with the Adper™ Single Bond Plus (SB) and Adper ™ Scotchbond SE (SE) adhesive systems and Filtek ™ Supreme Plus composite resin, using modified US Public Health Service criteria. A total of 97 restorations were placed in posterior teeth by two calibrated operators. Application of the materials followed manufacturers' instructions. The restorations were evaluated by two examiners at baseline and after one year. Statistical analyses were conducted using the proportion test at a significance level of 5% (p<0.05). All the restorations evaluated (ie, 100%) received an alpha rating for the criteria of marginal discoloration and marginal integrity at baseline. At one year, for marginal discoloration, 64.6% of SB and 61.2% of SE received an alpha rating. For marginal integrity, 72.9% of SB and 77.6% of SE received an alpha rating. The other restorations received bravo ratings for both criteria. None of the teeth that received the restorative systems presented caries lesions around the restorations. A total of eight teeth presented postoperative sensitivity one week after baseline, five with SB and three with SE; the symptom had disappeared one year later. One year later, composite resin restorations using either adhesive system showed satisfactory clinical performance.